(456 + 112) - x = 400 x - (203 + 303) = 34(283 - x) - 33 = 0 (536 + x) - 420 = 116437 - (227 + x) = 0 468 - 217 - x = 51
(456 + 112) - x = 400
x - (203 + 303) = 34
(283 - x) - 33 = 0
(536 + x) - 420 = 116
437 - (227 + x) = 0
468 - 217 - x = 51
Ответ(ы) на вопрос:
1. (456 + 112) - x = 400 568 - х = 400 х = 568 - 400 х = 168 2. x - (203 + 303) = 34 х - 506 = 34 х = 506 + 34 х = 540 3. (283 - x) - 33 = 0 283 - х = 0 + 33 283 - х = 33 х = 283 - 33 х = 250 4. (536 + x) - 420 = 116 536 + х = 116 + 420 536 + х = 536 х = 536 - 536 х = 0 5. 437 - (227 + x) = 0 227 + х = 437 - 0 227 + х = 437 х = 437 - 227 х = 210 6. 468 - 217 - x = 51 251 - х = 51 х = 251 - 51 х = 200
(456+112)-х=400 х-(203+303)=34 (283-х)-33=0 (536+х)-420=116 437-(227+х)=0 568-х=400 х=568-400 х=168 х-506=34 283-х=0 536+х=116+420 227+х=437 х=283 536+х=536 х=437-227 х=506+34 х=0 х=210 х=540 468-217-х=51 251-х=51 х=251-51 х=2 Немного съехало оформление)))))))))))))извиняюсь
Не нашли ответ?
Похожие вопросы